The league of the Aitolians - Grainger, John D., 1939- (Mnemosyne, Supplements, 1999)
The Aitolians have had a bad press, regarded as pirates and brigands, and their state as a pirate state built on terrorist tactics. This book treats them as what they really were, a normal Hellenistic state. They constructed an original and successful polity which provided peace and prosperity for its inhabitants, and played a major part in Greek history for a century and a half. The approach is chronological, beginning with the origin and formation of the league and its early expansion, and then dealing with its long duel with Macedon, and concluding with its destruction by Rome. This is the first full account of the history of the league which approaches it as an independent state rather than as the enemy of other states and peoples. It complements the standard histories of the other Hellenistic states.